2023
DOI: 10.3390/rs15133410
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Deep Learning and S2S Model for Improved Sub-Seasonal Surface and Root-Zone Soil Moisture Forecasting

Abstract: Surface soil moisture (SSM) and root-zone soil moisture (RZSM) are key hydrological variables for the agricultural water cycle and vegetation growth. Accurate SSM and RZSM forecasting at sub-seasonal scales would be valuable for agricultural water management and preparations. Currently, weather model-based soil moisture predictions are subject to large uncertainties due to inaccurate initial conditions and empirical parameterization schemes, while the data-driven machine learning methods have limitations in mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…As a branch of data-driven models, deep learning models can better address the insufficient ability of classical data-driven models to deal with nonlinear relationships in difficult situations. Recently, with the rapid development of deep learning models, it has been increasingly studied in the simulation and prediction of hydrological elements such as runoff, evapotranspiration, and soil moisture [26][27][28]. For instance, Castangia et al [29] explored the applicability of the transformer model to flood forecasting and found that the model has higher prediction accuracy than recurrent neural networks.…”
Section: Introductionmentioning
confidence: 99%
“…As a branch of data-driven models, deep learning models can better address the insufficient ability of classical data-driven models to deal with nonlinear relationships in difficult situations. Recently, with the rapid development of deep learning models, it has been increasingly studied in the simulation and prediction of hydrological elements such as runoff, evapotranspiration, and soil moisture [26][27][28]. For instance, Castangia et al [29] explored the applicability of the transformer model to flood forecasting and found that the model has higher prediction accuracy than recurrent neural networks.…”
Section: Introductionmentioning
confidence: 99%